The legacy of Arniston House - Huchu, T. L. (Huchu, T. L. Edinburgh nights., 2024)
Sixteen-year-old ghostalker Ropa works alongside Sir Callander to prevent the return of the dreaded Tall Man, who aims to merge the worlds of the living and the dead.